1966
DOI: 10.1002/ar.1091560112
|View full text |Cite
|
Sign up to set email alerts
|

The morphology of circulus arteriosus cerebri in rats

Abstract: Little has been reported concerning circulus arteriosus cerebri in adult rats. A study of rats' brains perfused with latex and fixed in formalin revealed the general configuration of a circular type pattern of the major ccrebral arteries in which all vessels were patent. N o major vessel was "string-like" and no circles were incomplete. Certain morphological features not described previously were observed. Included among the more significant of these were: (1) the asymmetrical origin of the posterior cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
2

Year Published

1968
1968
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 3 publications
2
60
2
Order By: Relevance
“…In our model, blood flow via the left vertebral artery was com pletely preserved, so the reason why there were cases that exhibited dyspnea is unclear. Since there are many variations in the circle of Willis in the rat (Brown, 1966), the ischemia may have been too se vere for these animals and, therefore, may have caused a dysfunction of the respiratory center in the brain stem. The lack of significant increase in the serum glucose concentration during ischemia indi cates the absence of epinephrine release from the adrenal glands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our model, blood flow via the left vertebral artery was com pletely preserved, so the reason why there were cases that exhibited dyspnea is unclear. Since there are many variations in the circle of Willis in the rat (Brown, 1966), the ischemia may have been too se vere for these animals and, therefore, may have caused a dysfunction of the respiratory center in the brain stem. The lack of significant increase in the serum glucose concentration during ischemia indi cates the absence of epinephrine release from the adrenal glands.…”
Section: Discussionmentioning
confidence: 99%
“…The right common carotid and right sub clavian arteries (the latter supplying the right vertebral artery) both arise from the innominate artery. The circle of Willis is well developed in rats, i.e., both the anterior and posterior communicating arteries are fairly large (Brown, 1966).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, cerebral blood flow of normal brain remains relatively constant despite acute rises of systemic blood pressure, except at abnormally high pressures. 16 Although it has been reported that the reactivity of the cortical vasculature to vasodilators in SHR is not different from that of NTR, 4 the actual values of cerebral blood flow in SHR have not been reported in the literature. In this study, it was found that rCBF and its distribution in SHR was almost identical with that of NTR, despite significantly increased levels of MABP.…”
Section: Spontaneously Hypertensive Ratsmentioning
confidence: 96%
“…Studies have been carried out in rats (Brown, 1966;Green, 1968), rats and mice (Firbas et al, 1973), mouse (Cook, 1965;Wiland, 1974;Szczurkowski et al, 2007), Guinea pigs (Ocal and Ozer, 1992), Guinea pigs and rabbits (Popesko et al, 1990), rabbits (Brehmer and Beleites, 1988), dogs (Miller et al, 1964), cats (McClure et al, 1973), porcupine (Aydin et al, 2005), Red squirrels (Aydin, 2008), Mongolian gerbils (Klachinka et al, 2008) and mole-rats . According to our knowledge there are no investigations on the circulus arteriosus cerebri of the ground squirrel (Spermophilus citellus) and this is the first study on this subject in ground squirrels.…”
mentioning
confidence: 99%